Efficacy and Safety of Mydriatic Regiments Used in Screening Retinopathy of Prematurity - Elisabeth Irma; Julie D. Barliana (Majalah Oftalmologi Indonesia, 2015)
Background: ROP screening must be done under pupil dilation to examine the ocular fundus, in order to allow diagnosis and staging of ROP. The objectives of this literature review are to compare the efficacy and safety of topical cyclopentolate, phenylephrine, tropicamide and the combination of these regiments in infants for ROP screening. Methods: The search was conducted through electronic databases providing journal articles with keywords: cyclopentolate, phenylephrine and tropicamide on pupil dilation and systemic side effects in infants on screening Retinopathy of prematurity.The baseline of pupil diameter, frequency of instillation, mean difference amount of dilated pupil size and diameter of the pupil in 30 or 45 minutes and 60 minutes are presented in outcome. Results: The mydriatic agents used in this literature review were phenylephrine, tropicamide, cyclopentolate and the combination of those regiments. Doses of mydriatic agents used in this review are variables. The lowest dose for phenylephrine is 1%, cyclopentolate is 0.2% and tropicamide is 0.5%. The highest dose for phenylephrine is 2.5%, cyclopentolate is 1.0 % and tropicamide is 10 %. The use of mydriatic regiments during newborn ophthalmic examinations has been associated with systemic side effects. Most reports have implicated the sympathomimetic component of the mydriatic solutions as the hypertensive agents. Conclusion: Using only cyclopegic regimens did not produce adequate mydriasis in infants. The combination of low concentration sympathomimetic (phenylephrine 1%) and parasympatholytic (Cyclopentolate 0.2 %) produces adequate pupillary dilation and does not cause an increase in blood pressure and heart rate.